Physicochemical Parameters and Heavy Metal Concentration in Water at the Mokesh Beel of Bangladesh - Barmon, PC; Islam, MS; Kabir, MH (Journal of Environmental Science and Natural Resources, 2019)
The study investigated physicochemical parameters and heavy metal concentrations in water of the Mokesh beel during January to June 2016. Samples were collected from 3 different locations and analyzed in the laboratory of the Department of Environmental Science and Resource Management, MBSTU, Tangail and BINA, Mymensingh. Results showed that EC and TDS were varied from 645-688μS/cm and 541-586mg/l, respectively indicated high ionic concentration, whereas DO of all stations ranged from 4.1-5.5mg/l represents low organic waste, and pH (7.25-7.55) of all stations showed alkaline nature. In case of heavy metal concentration Pb, Cd, Cu, Zn and Cr were within the standard level. The result concludes that the water can be used for different purposes but heavy metals can be accumulated in fish flesh, consequently affect the human health. To maintain the water quality and conserve the aquatic life, proper measures should be taken to prevent pollutants intrusion into the beel. J. Environ. Sci. & Natural Resources, 11(1-2): 1-8 2018